2000
DOI: 10.1162/105474600566600
|View full text |Cite
|
Sign up to set email alerts
|

Small-Group Behavior in a Virtual and Real Environment: A Comparative Study

Abstract: This paper describes an experiment that compares behavior in small groups when its members carry out a task in a virtual environment (VE) and then continue the same task in a similar, real-world environment. The purpose of the experiment was not to examine task performance, but to compare various aspects of the social relations among the group members in the two environments. Ten groups of three people each, who had never met before, met first in a shared VE and carried out a task that required the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
187
2
1

Year Published

2001
2001
2001
2001

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 304 publications
(204 citation statements)
references
References 11 publications
14
187
2
1
Order By: Relevance
“…The main finding of that study that is relevant here is that whereas collaborators in the FtF condition experienced that they participated equally, in the ItD condition they reported that they contributed unequallyFdespite being unaware of what type of system the other participant was using (as was the case in the Slater et al [7] study mentioned above, and in the study we report here).…”
Section: Previous Studiessupporting
confidence: 50%
See 4 more Smart Citations
“…The main finding of that study that is relevant here is that whereas collaborators in the FtF condition experienced that they participated equally, in the ItD condition they reported that they contributed unequallyFdespite being unaware of what type of system the other participant was using (as was the case in the Slater et al [7] study mentioned above, and in the study we report here).…”
Section: Previous Studiessupporting
confidence: 50%
“…The questions, which will in part be reproduced below, were often based on previous studies (esp. [7,11]) in order to build on and extend earlier results.…”
Section: Technical Description and Study Designmentioning
confidence: 89%
See 3 more Smart Citations